British Diplomats, Bakufu and Japanese Civil War: friends or foes - Fathil, Fauziah (2014)
Being the most dominant foreign power in nineteenth century Japan, Britain is often believed to have been behind the rise and eventual success of anti-Bakufu movement in a war against Tokugawa Shogunate. Britain, as argued by some, had indirectly supported the anti-Bakufu forces leading to the collapse of the Shogunate and establishment of new Imperial government in 1868. While there had been some events or developments cited to support this view, the general British diplomats’ stance towards either the Bakufu or its opponents, as this paper attempts to show, was that of neutrality. Their attitude and views towards both parties with regard to different matters varied, ranging from condemnatory to complimentary. This paper aims to highlight the general neutral attitude of the British diplomats, and at the same time exceptional views as expressed by a few, such as diplomat Ernest Satow in favour of the anti-Bakufu forces. Using mainly archival materials and diplomatic correspondence, this paper will demonstrate not only the views of British diplomats towards the Bakufu and anti-Bakufu forces as Japanese politics underwent changes, but also related issues or concerns which might have influenced their attitude and stance towards both.